Subinhibitory Clindamycin Differentially Inhibits Transcription of Exoprotein Genes in Staphylococcus aureus - Herbert, Silvia (American Society for Microbiology, 2001)
It has long been known that certain antibiotics, at subinhibitory concentrations, differentially inhibit the synthesis of α-hemolysin and other staphylococcal virulence factors. In this report, we show that subinhibitory clindamycin (SBCL) eliminates production of nearly all exoproteins by Staphylococcus aureus but has virtually no effect on cytoplasmic proteins. The effect was abolished by a gene conferring resistance to macrolides-lincosamides-streptogramin B, showing that differential inhibition of protein synthesis is responsible; remarkably, however, subinhibitory clindamycin blocked production of several of the individual exoprotein genes, including spa (encoding protein A), hla (encoding α-hemolysin), and spr (encoding serine protease), at the level of transcription, suggesting that the primary effect must be differential inhibition of the synthesis of one or more regulatory proteins. In contrast to earlier reports, however, we found that subinhibitory clindamycin stimulates synthesis of coagulase and fibronectin binding protein B, also at the level of transcription. agr and sar expression was minimally affected by subinhibitory clindamycin. These effects varied from strain to strain and do not seem to be responsible for the effects of subinhibitory clindamycin on the overall exoprotein pattern.